Machine for making pineapple roll tarts. - Shamsuddin, Rosnah; M. , Nur Adila Akma; Pua, Ming Yee (2012)
Majority of pineapple roll tarts in Malaysia are produced manually. Therefore, the productions are slow and unable to meet the market demand. The most critical parts in making the pineapple roll tarts are the rolling and wrapping processes. A rolled tart making machine (PI 201 1700016) was designed to solve this problem. It is essential for the efficient mass production of pineapple roll tarts': The machine is simple, feasible, hygienic, high production rate and a cost saving piece of equipment. Moreover, it is a very practical machine as the process of assembling and cleaning is easy. The machine was developed to full fill the needs of a small scale pineapple tart producer. The machine comprises of 3 main processing parts which are the feeding unit, extrusion unit and cutting unit. The dimension of the machine is 820 mm (L) x 420 mm (W) x 520 mm (H). The pastry and jam are placed into the cylinder feeding unit and pushed by a piston. Then they are extruded concurrently from the nozzle horns. The production rates of this machine are in the range of 1000 pieces per hour depending on the speed of machine.